Resistência biótica ou abiótica? A resposta de uma macrófita invasora. - Souza, Douglas Costa de (2017)
The invasion process can be influenced or prevented by the action of biotic resistance offered by native species. Such influence can be enhanced by priori planting of individual of native species. The present work aimed to analyze the response of the invasive macrophyte Hydrilla verticillata against biotic resistance (offered by the native macrophyte Egeria najas) and the concentration of organic matter. Through a cross-factorial experiment such a response was investigated, where individuals of the native species were planted one month earlier than the individuals of the invasive species to achieve the priority effects. To analyze the data were used GLM (generalized linear models), that statistically tested how the two factors of the present work influenced the biological traits of invasive species. The results showed that all the biological traits studied, except root/ shoot ratio, were significantly influenced by sediment type and, above all, by biotic resistance. H. verticillata can grow in sites with high organic matter concentration, however, a priori biotic resistance reduces its biomass. This can be used for management programs of this invasive species, as well as being extrapolated for the prevention of invasion processes.